The relationship between agricultural students’ behavior and the factors experiencing of academic integrity violations in cultivating new norms - Nurul Nuraliya Shahrai; Mohamad Nizam Nazarudin; Wijaya Kamal Ramlan; Abdul Hair Beddu Asis; Ahmad Norazhar Mohd Yatim; Hadzariah Ismail (Universiti Utara Malaysia, 2021)
The aim of this study is to determine the relationship between students‟ behavior and the factors experiencing of academic integrity violations in cultivating new norms. From the whole population of student living in Lestari College, Universiti Malaysia Sabah, Sandakan Campus, 122 out of 205 students participated voluntarily which involved by 61 females and 31 males. Of the participants, 61 students from crop production (HG34), 35 from horticulture and landscaping (HG35) and 26 students from livestock production (HG36). Descriptive data of questionnaires were recorded by using open-ended answers for behaviors and a five-point Likert-type instrument used to identify the reason doing academic integrity violations which ranged strongly disagreed to strongly agreed. There was significant different between gender (p<0.05) but no significant difference between each study programme. In term of correlation, this study found there was relationship between gender and behavior QB7 (r=0.300, p<0.05) related to copy content from another sources. Besides, correlation could be found between QB4 and QV2 (r=0.231, p<0.05) which related to behavior in obtaining content from another student‟s material and make it as their own because of having a lot of assignments to do at the same time. There was another significant correlation between QB8 and QV4 (r=-.186, p<0.05) as students help another person to compose ideas affected by unclear explanation from lecturers. In our study, a slight tendency to academic integrity dishonesty behavior was found correlated with several factors. However, this current study was uncertain detail in gender and programme disparities for each provided questionnaires.